Cochrane Database of Systematic Reviews 2014
DOI: 10.1002/14651858.cd011313
|View full text |Cite
|
Sign up to set email alerts
|

Yttrium-90 microsphere radioembolisation for unresectable hepatocellular carcinoma

Abstract: To determine the benefits and harms of Y-90 microsphere radioembolisation either as a monotherapy or in combination with other systemic or locoregional therapies versus placebo, no treatment, or other similar systemic or locoregional therapies for patients with unresectable hepatocellular carcinoma.1 Yttrium-90 microsphere radioembolisation for unresectable hepatocellular carcinoma (Protocol)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…In addition to the high concordance among monozygotic twins compared with dizygotic twins with PBC, the strong association with human leukocyte antigen alleles, which vary by ethnicity, supports a genetic cause of inherited risk . Despite progress, only an estimated 15% of the variability of the disease has been accounted for by genetic studies .…”
Section: Etiology Of Primary Biliary Cholangitismentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the high concordance among monozygotic twins compared with dizygotic twins with PBC, the strong association with human leukocyte antigen alleles, which vary by ethnicity, supports a genetic cause of inherited risk . Despite progress, only an estimated 15% of the variability of the disease has been accounted for by genetic studies .…”
Section: Etiology Of Primary Biliary Cholangitismentioning
confidence: 99%
“…(10)(11) In addition to the high concordance among monozygotic twins compared with dizygotic twins with PBC (5) , the strong association with human leukocyte antigen alleles, which vary by ethnicity, supports a genetic cause of inherited risk. (12)(13)(14)(15)(16)(17)(18)(19)(20) Despite progress, only an estimated 15% of the variability of the disease has been accounted for by genetic studies. (21) Environmental risks have been suggested by several large case-control cohort studies that have found associations with urinary tract infections, reproductive hormone replacement, nail polish, and past cigarette smoking.…”
Section: Preamblementioning
confidence: 99%
“…However, surgical resection is only suitable for early‐stage patients with well‐preserved liver function . In the majority (>70%) of HCC patients, the cancer has progressed to stages that make them ineligible for surgical resection or liver transplantation at the time of presentation and diagnosis …”
Section: Current Treatment Modalities For Unresectable (Intermediate mentioning
confidence: 99%
“…8,15,16,18 In the majority (>70%) of HCC patients, the cancer has progressed to stages that make them ineligible for surgical resection or liver transplantation at the time of presentation and diagnosis. 8,[19][20][21][22] For patients with unresectable intermediate-stage HCC (ie, BCLC stage B disease), transarterial chemoembolisation (TACE)-a type of locoregional therapy-is the first line of treatment recommended as per AASLD and EASL guidelines. Transarterial therapies take advantage of the fact that hepatic tumours receive their blood supply almost exclusively from the hepatic artery.…”
Section: Current Treatment Modalities For Unresectable (Intermediatmentioning
confidence: 99%